ITS gene based molecular genotyping of Nepeta sheilae Hedge & R.A. King (Lamiaceae) endemic to Saudi Arabia (Bangladesh Journal of Plant Taxonomy, 2020)
Abstract not availableBangladesh J. Plant Taxon. 27(1): 185-189, 2020 (June)